1997
DOI: 10.1063/1.119976
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy of dispersed carbon nanotubes induced by an electric field

Abstract: Carbon nanotubes dispersed in ethanol are aligned by an electric field. Due to the orientation of these elongated particles, the dispersion exhibits anisotropic behaviour.Transmission experiments show rotation of the linear polarisation of an incident laser beam. Alignment and relaxation times and the influence of the magnitude of the electric field have been measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(82 citation statements)
references
References 12 publications
(1 reference statement)
3
78
0
1
Order By: Relevance
“…It is found that the absorption threshold is significantly higher (by about 0.12 eV in the (6, 0) tubule and 0.60 eV in the (7, 0) tubule) for the electronic field E B along the tubule axis than for that vertical to the axis. The optical anisotropy of dispersed CNTs induced by an electric field has been observed in the experiment, 63 and may be used to determine the orientational ordering of the CNTs.…”
Section: E(t) ) (1/ πT H) E -(T/t H)mentioning
confidence: 99%
“…It is found that the absorption threshold is significantly higher (by about 0.12 eV in the (6, 0) tubule and 0.60 eV in the (7, 0) tubule) for the electronic field E B along the tubule axis than for that vertical to the axis. The optical anisotropy of dispersed CNTs induced by an electric field has been observed in the experiment, 63 and may be used to determine the orientational ordering of the CNTs.…”
Section: E(t) ) (1/ πT H) E -(T/t H)mentioning
confidence: 99%
“…Numerically, the most favorable approach is to use Eq. (14): after choosing a suitable coordinate system, we apply an electric field in the x direction and calculate the cluster polarization by solving Eq. (11).…”
Section: B Static Polarizability and Orientational Energy Of Dipole mentioning
confidence: 99%
“…This self-assembly process can be spontaneous in the case of favorable thermodynamic conditions and suitable effective particle-particle interactions, [3][4][5][6][7][8][9][10] but can also be steered and further manipulated by external fields. Rodlike particles in a liquid dispersion, for instance, can spontaneously align at sufficiently high concentrations solely due to their excluded volume interactions, 11 but their self-organisation has also been driven by external magnetic or electric fields, [12][13][14][15][16] by substrates that preferentially orient the rods, 17,18 or by fluid flow. 19 Also, more complicated shapes have been synthesized and studied, for instance, dumbbells, 2,[20][21][22] cubes, 23 and bowls.…”
Section: Introductionmentioning
confidence: 99%
“…Many procedures have been proposed to achieve the desired highly ordered structures, e.g., by using systems with substrates or templates, 1 applying external electric, or magnetic fields [2][3][4][5][6] to particles with anisotropic response to these fields, or by using a fluid flow 7 to align the particles. One of the most widely used techniques, however, is the design and manipulation of particle-particle interactions, which can result in spontaneous self-assembly.…”
Section: Introductionmentioning
confidence: 99%